Carbon Emission Disclosure and Its Impact on Developing Countries - Indah Fajarini Sri Wahyuningrum; Linda Agustina; Muhammad Ihlashul’amal; Kuat Waluyo Jati; Suci Sularsih; Syaiful Anwar; Sriningsih Sriningsih (School of Postgraduate Studies, Diponegoro Univer, 2025)
This study aims to explore carbon emission disclosure practices in Indonesia, and extensive testing by providing one representative variable for each group of factors thought to be influential. Using 113 analysis units as research samples of non-financial public companies listed on the Indonesia Stock Exchange (BEI) in 2019-2021. Data collected from annual and sustainability reports and analyzed using descriptive statistical tests and multiple linear regression. The descriptive analysis shows that the level of carbon emission disclosure in Indonesia is still low but is on a stable trend, increasing from year to year. Environmental performance can increase carbon emission disclosure. Companies with good environmental performance will proudly reveal their success through carbon emission disclosures. In addition, young companies were found to have better levels of carbon disclosure than older companies. Likewise, companies with high media visibility do not disclose carbon emissions better than companies with low media visibility. The results of this study have met the adequacy of robustness and endogeneity tests through other regression methods and help managers use their environmental performance to design information disclosure policies related to carbon emissions. The research results show the need of carbon emission disclosure guidelines by regulators/government. Moreover, Indonesia as the country is predicted to be the slowest to reach net-zero carbon compared to other countries.